2019
DOI: 10.1002/anie.201901873
|View full text |Cite
|
Sign up to set email alerts
|

A DNAzyme‐Based Colorimetric Paper Sensor for Helicobacter pylori

Abstract: The reliable detection of pathogenic bacteria in complex biological samples using simple assays or devices remains a major challenge. Herein, we report a simple colorimetric paper device capable of providing specific and sensitive detection of Helicobacter pylori (H. pylori), a pathogen strongly linked to gastric carcinoma, gastric ulcers, and duodenal ulcers, in stool samples. The sensor molecule, an RNA‐cleaving DNAzyme obtained through in vitro selection, is activated by a protein biomarker from H. pylori. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 37 publications
(5 reference statements)
1
96
0
Order By: Relevance
“…The reduced catalytic activity of LP1FQ is not favourable for direct translation to rapid fluorescent detection. However, a variety of signal production mechanisms have been devised specifically for RNA‐cleaving DNAzymes [13, 20] . It is conceivable that some of these strategies can be used to convert the L. pneumophila ‐specific DNAzyme into a rapid and sensitive sensing system for on‐site detection of L. pneumophila in cooling tower water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced catalytic activity of LP1FQ is not favourable for direct translation to rapid fluorescent detection. However, a variety of signal production mechanisms have been devised specifically for RNA‐cleaving DNAzymes [13, 20] . It is conceivable that some of these strategies can be used to convert the L. pneumophila ‐specific DNAzyme into a rapid and sensitive sensing system for on‐site detection of L. pneumophila in cooling tower water.…”
Section: Discussionmentioning
confidence: 99%
“…RFDs have been selected for a handful of common bacteria including Escherichia coli , [18] Clostridium difficile , [19] Helicobacter pylori , [20] and Klebsiella pneumoniae [21] . It has been well demonstrated that RFDs can be used as molecular recognition elements for the design of biosensors and bioassays for bacterial detection [18–25] . For example, RFD‐EC1, which was first reported in 2011 for E. coli , has been successfully incorporated into multiple biosensing platforms [25–33] .…”
Section: Introductionmentioning
confidence: 99%
“…Using the RNA‐cleaving DNAzyme, Brennan and co‐workers designed a colorimetric paper device for specific and sensitive detection of Helicobacter pylori . The DNAzyme‐enabled colorimetric paper device worked well as point‐of‐care diagnostics for monitoring pathogens in complex real samples and maintained full functions even after 130 day storage at ambient temperature (Figure B) . In addition, as the secondary or tertiary structures of DNAzyme had well been demonstrated, many detection strategies were designed based on the structural modifications.…”
Section: Dna Nanomaterialsmentioning
confidence: 99%
“…B) Working principle of the DNAzyme solution‐based test and the selectivity test using stool samples spiked with various bacterial species. Adapted with permission . Copyright 2019, Wiley‐VCH Verlag GmbH &Co. KGaA, Weinheim.…”
Section: Dna Nanomaterialsmentioning
confidence: 99%
“…At present, numerous intelligent detecting equipment have been supplied with plentiful sensors, extending their practical applications into diverse domains including industrial production, marine exploration, environmental protection, medical diagnosis, bioengineering, cosmic exploration, smart home. [1][2][3] With the growing demands for applications in the information age, the expectation and idealized requirements about abundant sensing performance of detecting range, accuracy, and stability have been gradually amplified. Aimed at the monitoring necessities of gas, stress, and temperature in the presented work provides state-of-the-art advances in 3D printed strain sensors, which is organized in three following sections.…”
Section: Introductionmentioning
confidence: 99%